2019
DOI: 10.1186/s10086-019-1806-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of bamboo scrimber: a literature review

Abstract: Bamboo fiber-based composite made from crushed bamboo fiber, termed bamboo scrimber, has gained particular interest of researchers and manufacturers on account of its excellent mechanical characteristics and design. This paper reviewed the available literature on the state of the art of bamboo scrimber including the developing history and current production technology of high-performance bamboo scrimber. The results of analytical and experimental investigations illustrate the effects of bamboo species, defiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(71 citation statements)
references
References 35 publications
0
70
1
Order By: Relevance
“…Bamboo scrimber is a new type of bamboo-based composite that is manufactured by hot or cold pressure on the bamboo bundle. The development of bamboo scrimber not only improves the utilization of bamboo, but also provides a good option for structural engineering due to its excellent performance [ 5 , 6 ]. Indeed, numerous studies have shown that bamboo scrimber has good application prospects in structural buildings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo scrimber is a new type of bamboo-based composite that is manufactured by hot or cold pressure on the bamboo bundle. The development of bamboo scrimber not only improves the utilization of bamboo, but also provides a good option for structural engineering due to its excellent performance [ 5 , 6 ]. Indeed, numerous studies have shown that bamboo scrimber has good application prospects in structural buildings.…”
Section: Introductionmentioning
confidence: 99%
“…However, bamboo is rich in sugar and has abundant starch, which leads to its high moisture absorption and poor biological durability. Therefore, bamboo scrimber absorbs water easily and can form cracking defects under outdoor conditions, which greatly reduces the safety coefficient of the bamboo scrimber in engineering utilization [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process causes the formation of new composite material with different physical, chemical, and mechanical properties. In some cases, both mechanisms may occur at the same time in some processes, like in the production of compressed wood-polymer composites [ 22 ] and bamboo scrimber [ 23 , 24 , 25 ]. The final density is controlled by the densification method.…”
Section: Densification Conceptmentioning
confidence: 99%
“…The increase of density may be related to the closure of bamboo voids such as vessels, parenchymas, and fiber lumens caused by high-pressure and hot-pressing processes [ 25 , 75 ], or the presence of solid resin particles in the cavities. The microstructural analysis of engineered bamboo scrimber at different densities conducted by Yu (2017) [ 75 ], shows that when the scrimber density is low, for example at 850 kg/m 3 , the structure is irregular, which led to deficient fiber bonding.…”
Section: Densification In Bamboo-based Panelsmentioning
confidence: 99%
“…The current methods for preparing porous bamboo are rarely reported. The content of lignin is about 30% of the total content of bamboo, and it is cross‐linked with various polysaccharides in bamboo to give structural support, which cannot be ignored . The separation of lignin destroys and weakens the native structure of bamboo, posing challenges and impractical for the handling and manufacture of large substrates .…”
Section: Introductionmentioning
confidence: 99%